Toxicity test of rose periwinkle (Catharanthus roseus) leaves endophytic bacteria using Brine Shrimp Lethality Test (BSLT) method - FAUZIAH FAUZIAH; MAULINASARI MAULINASARI; ESSY HARNELLY; YULIA SARI ISMAIL; LENNI FITRI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fauziah F, Maulinasari, Harnelly E, Ismail YS, Fitri L. 2021. Toxicity test of rose periwinkle (Catharanthus roseus) leaves endophytic bacteria using Brine Shrimp Lethality Test (BSLT) method. Biodiversitas 23: 171-177. Endophytic bacteria can be obtained from plants and may have the same ability as their host to produce secondary metabolites. This study aimed to determine the toxicity of endophytic bacterial extract from rose periwinkle (Catharanthus roseus) leaves using the Brine Shrimp Lethality Test (BSLT) method to determine their secondary metabolite contents. A toxicity test was carried out using Artemia salina shrimp larvae. The effect of the extract was determined based on the shrimp larvae mortality percentage using four concentration levels of 1000 ppm, 750 ppm, 500 ppm, and 250 ppm. Furthermore, the LC50 value of the extract against shrimp larvae was analyzed using SPSS software to obtain eight isolates of endophytic bacteria from Catharanthus roseus leaves. Macroscopic observations showed different characters, and five isolates were Gram-positive bacteria, while three were Gram-negative bacteria. The BETD5 isolate had the lowest LC50 value of 413,590 ppm, and the secondary metabolites of BETD5 extract were alkaloid and saponin. The molecular identification indicated that BETD5 had the highest identity percentage of 99.38% with Staphylococcus arlettae strain NR_036903, Staphylococcus gallinarum strain LMG 19119, Staphylococcus sp. strain Fop 222, Staphylococcus gallinarum strain E2 and Staphylococcus sp. strain MFC2.